2008
DOI: 10.1002/pola.22869
|View full text |Cite
|
Sign up to set email alerts
|

Highly fluorescent mono‐substituted poly(arylacetylene)s containing tolane chromophores

Abstract: A new class of highly fluorescent mono-substituted polyarylacetylenes (P1-P3) has been successfully prepared with good yields and high molecular weights from a series of phenylethynylene-substituted arylacetylenes (M1-M3), using Wbased catalyst. These polymers are readily soluble in common organic solvents (e.g., THF, toluene, and chloroform) and thermally stable up to $350 8C. Both 1 H NMR and IR studies confirmed that all the monomers were selectively polymerized at the terminal triple bond. The 1 H NMR resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Therefore, the chemical yields and polymer properties of P4–P6 do not strictly derive from the activation source (irradiation vs. metal catalysis), but appear to be related to the nature of the growing carbon chain imposed by the ortho substituent in the course of the polymerization process. In the case of transition metal catalysis, it has been suggested that undesired chain transfer and termination events are limited in bulky propagating species 23–25. Remarkably, poly( o ‐CF 3 PA) obtained by catalysis of W(CO) 6 under UV irradiation exhibited higher MWs than poly( m ‐CF 3 PA) or poly( p ‐CF 3 PA), and the M w values increased with decreasing monomer concentration in solution 26…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the chemical yields and polymer properties of P4–P6 do not strictly derive from the activation source (irradiation vs. metal catalysis), but appear to be related to the nature of the growing carbon chain imposed by the ortho substituent in the course of the polymerization process. In the case of transition metal catalysis, it has been suggested that undesired chain transfer and termination events are limited in bulky propagating species 23–25. Remarkably, poly( o ‐CF 3 PA) obtained by catalysis of W(CO) 6 under UV irradiation exhibited higher MWs than poly( m ‐CF 3 PA) or poly( p ‐CF 3 PA), and the M w values increased with decreasing monomer concentration in solution 26…”
Section: Resultsmentioning
confidence: 99%